1897
DOI: 10.1111/j.1469-7998.1897.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

1. On the Myology of the Terrestrial Carnivora.—Part I. Muscles of the Head, Neck, and Fore‐Limb

Abstract: MYOLOGY OF THE TEKEESTRIAL CARNIVORA. 373 897.] iiTOLOGY or the terrestrial carmvora. * 'Anat. des Kanincliens.' * It should, however, be borne in mind that the ccntrnlis is very easily overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
3
1

Year Published

1942
1942
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(151 citation statements)
references
References 6 publications
5
116
3
1
Order By: Relevance
“…carnivores and ungulates: see, e.g. Windle & Parsons 1897). However, this clearly seems to be a derived condition for mammals because the numerous mammalian taxa with three heads include phylogenetically plesiomorphic mammals such as monotremes and marsupials (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…carnivores and ungulates: see, e.g. Windle & Parsons 1897). However, this clearly seems to be a derived condition for mammals because the numerous mammalian taxa with three heads include phylogenetically plesiomorphic mammals such as monotremes and marsupials (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the terminology associated with the short digital flexors suffers from a lack of standardization, making it difficult to conduct a comprehensive, family‐level comparison. However, according to Windle & Parsons (1897), the majority of carnivores retain a full complement of mm. flexores digitorum breves, and this is the case in Ailurus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1999), such as perissodactyls and artiodactyls, its presence in some carnivores, including Ailurus , is likely to be primitive (Fig. 4; Table 4) (Gratiolet, 1867; Macalister, 1873c; Beddard & Treves, 1889; Windle & Parsons, 1901; Campbell, 1935, 1936; Getty, 1975b; Sisson, 1975; Macdonald et al. 1985; Nickel et al.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has also been used to reconstruct the muscular patterns in a number of extinct sloths, e.g., Paramylodon, Nothrotheriops, Megatherium, Mylodon (Naples1987,1989; Bargo,2001; Bargo et al,2006). It should be noted that previous dissections of the extant sloths (MacIntosh,1873,1874; Windle and Parsons,1899; Naples1982,1985; Sicher,1944) have indicated that the m. masseter consists of two layers: a superficial, five‐part m. masseter superficialis and a deep m. masseter pars profunda. As the emphasis of this study is upon a fossil sloth taxon, m. masseter pars profunda is not reconstructed and all references herein to m. masseter refer solely to m. masseter superficialis.…”
Section: Methodsmentioning
confidence: 97%